ANALISIS BENTUK GOLONGAN PUTIH DALAM PEMILIHAN UMUM DI KELURAHAN BETUNGAN KOTA BENGKULU - Linda Astuti (Professional: Jurnal Komunikasi dan Administrasi Publik, 2020)
This study tries to identify and analyze the Behavior of the White Group in the General Election in Betungan Village, Bengkulu City. Understanding white behavior researchers using behavior change theory (KurtLewin) argue that human behavior is a state of balance between the driving forces and the restining forces. The research method used by the researcher is descriptive qualitative research method with the informants of Betungan Village residents and election administrators. The residents of Betungan Village did not participate in the voting because many had moved on the election day, showing the lack of education and political awareness that the newcomers of Betungan Village have. The residents of Betungan Village are tired of the promises of future leaders that have absolutely no proof. The residents of Kelurahan Betungan are busy with personal matters rather than participating in the general election, for them participating in the general election is not very important.